2019
DOI: 10.1002/hbm.24584
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional white‐matter networks in medicated and unmedicated benign epilepsy with centrotemporal spikes

Abstract: Benign epilepsy with centrotemporal spikes (BECT) is the most common childhood idiopathic focal epilepsy syndrome, which characterized with white‐matter abnormalities in the rolandic cortex. Although diffusion tensor imaging research could characterize white‐matter structural architecture, it cannot detect neural activity or white‐matter functions. Recent studies demonstrated the functional organization of white‐matter by using functional magnetic resonance imaging (fMRI), suggesting that it is feasible to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 63 publications
9
59
0
1
Order By: Relevance
“…Taken together, these findings suggest that there are no fundamental barriers or direct sources of evidence against the possibility of detecting neural activities of BOLD‐fMRI in WM (Gawryluk, Mazerolle, & D'Arcy, ). To date, many psychiatric and neurological disorders are characterized by WM functional abnormalities (Ji et al, ; Jiang et al, ; Jiang et al, ; Wang et al, ). It is therefore important to explore WM functional networks to allow for fMRI‐based investigations of WM brain disorders, such as multiple sclerosis (He et al, ), and WM dementia (Filley, ), which may allow further insight into our understanding of the pathological mechanisms of different neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these findings suggest that there are no fundamental barriers or direct sources of evidence against the possibility of detecting neural activities of BOLD‐fMRI in WM (Gawryluk, Mazerolle, & D'Arcy, ). To date, many psychiatric and neurological disorders are characterized by WM functional abnormalities (Ji et al, ; Jiang et al, ; Jiang et al, ; Wang et al, ). It is therefore important to explore WM functional networks to allow for fMRI‐based investigations of WM brain disorders, such as multiple sclerosis (He et al, ), and WM dementia (Filley, ), which may allow further insight into our understanding of the pathological mechanisms of different neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Ji et al found that patients with Parkinson's disease showed increased small‐worldness in the WM functional network (Ji et al, ). Moreover, brain function profiles of WM function, including power spectra, coupling of WM and GM functional connectivity were found to be disrupted in various brain disorders, such as pontine stroke, Alzheimer's disease, and epilepsy (Jiang et al, ; Makedonov, Chen, Masellis, & MacIntosh, ; Wang et al, ). However, such previous studies focused on the extant functional modules and large‐scale networks in WM; used relatively small sample sizes; and failed to offer direct evidence for the different roles played by functional connectomes within WM and GM.…”
Section: Introductionmentioning
confidence: 99%
“…These and other relevant contributions were included in a recent Perspective by Grajauskas et al (2019) who argue strongly that WM activity should not be treated as a nuisance regressor but instead be recognized as important in analyses of brain function. Moreover, an increasing number of studies have reported that alterations of WM networks are associated with brain disorders including schizophrenia, Parkinson’s disease and epilepsy (; Ji et al, 2019 ; Jiang et al, 2019 , 2018 ). Taken together, these findings indicate that WM-GM and WM-WM correlations reveal an underlying organization and suggest further investigations are justified of the possible contributions of WM signals to the identification of well-established brain networks that by convention consist of GM alone.…”
Section: Introductionmentioning
confidence: 99%
“…In the 30-80 Hz band, the PCC region was inactivated, while in the 80-250 Hz band, the MFC region was inactivated. Some studies suggest that frequent interictal spike discharges, especially during sleep, may interfere with the development of white matter in children, thereby causing changes in the neuromagnetic field [13,39]. During the resting state, the brain is active in an organized way, and this active network is called the default mode network (DMN), which includes the PCC, the dorsal medial prefrontal cortex (middle frontal gyrus, superior frontal gyrus), dorsal anterior cingulate gyrus, and bilateral angular gyrus [40].…”
Section: Source Localizationmentioning
confidence: 99%